2023
DOI: 10.3390/ijerph20054160
|View full text |Cite
|
Sign up to set email alerts
|

PTSD and Partial PTSD among First Responders One and Five Years after the Paris Terror Attacks in November 2015

Abstract: Following the Paris terror attacks in November 2015, a large number of first responders (FR) were mobilized and consequently were at risk of developing posttraumatic stress disorder (PTSD). Based on the ESPA 13 November survey, the objectives of this study were to 1) describe the prevalence of PTSD and partial PTSD in FR five years after the attacks, 2) describe the changes in PTSD and partial PTSD from one to five years after the attacks, and 3) examine factors associated with PTSD and partial PTSD five years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Stigma related to getting help can be combated by educating EMS workers on mental health impacts. For example, Prioux et al (2023) found that first responders over 45 years of age who did not know about the psychological effects of traumatic experiences were at a higher risk for developing partial PTSD across 5 years. Education, multicenter screening, early support management, access to institutional support, and psychological and counseling assistance are essential to preventing PTSD (Rybojad et al, 2016).…”
Section: Implications For Practicementioning
confidence: 99%
“…Stigma related to getting help can be combated by educating EMS workers on mental health impacts. For example, Prioux et al (2023) found that first responders over 45 years of age who did not know about the psychological effects of traumatic experiences were at a higher risk for developing partial PTSD across 5 years. Education, multicenter screening, early support management, access to institutional support, and psychological and counseling assistance are essential to preventing PTSD (Rybojad et al, 2016).…”
Section: Implications For Practicementioning
confidence: 99%
“…People typically view first responders as dedicated professionals, essential to maintaining order and providing crucial assistance in emergency situations. Often, their work is so stressful that in some cases they end up suffering with PTSD years after their efforts [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%